Dynamics Analysis Model of Nature Tourism System Development In Bogani Nani Wartabone National Park of Gorontalo Province - Bempah, Irwan (Jurnal Manajemen, 2018)
In general, the interacting elements in the nature tourism system in NaniWartaboneBogani National Park (TNBNW) are population; some tourist visitors; community income; income tax; land use/forest cover and development policy direction. Simulation results show the population is predicted to increase until reaching 380,357 people in 2030. In the optimistic scenario, the population in 2013 is predicted as many as 158,195 people and will increase to 308,149 in 2030. In the optimistic scenario of the number of tourists in 2013 predicted as many as 25,806 people and will increase to 145,215 people by 2030. Community income in 2008 of Rp 12,000,000 is expected to increase to Rp 78,806,894 in 2030. Optimistic scenario of community revenues in 2013 is estimated at Rp 69,656,421 will increase to Rp 484,520 .719 in 2030. In an optimistic scenario subsidy in 2013 is estimated at Rp 22,107,690 and will increase to Rp 175,305,853 in 2030. The optimistic scenario of primary forest cover in 2013 is estimated to cover 136,040 ha and will decrease slightly to 134,910 ha in 2030.